ENGLISH LANGUAGE TEACHERS’ CONTINUOUS PROFESSIONAL DEVELOPMENT OBSTACLES - Mohammed, Abrar Kedir; Gutema, Hailu (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
The goal of this study was to investigate the needs for and barriers to the ongoing professional development of elementary school English language teachers. Data collection techniques included surveys, interviews, and classroom observations. Surveys of 64 randomly chosen English language teachers in primary schools were used to get the quantitative data. In order to verify the information gathered from the surveys, interviews were done with principals, trainers, and volunteer English language teachers who took part in the surveys, which included surveys, interviews, and classroom observations. Surveys of 64 randomly chosen English language teachers in primary schools were used to get the quantitative data. In order to verify the information gathered from the surveys, interviews were done with principals, trainers, and volunteer English language teachers who took part in the surveys. The data were analyzed using a Quan-qual approach. The statistical analysis of the data was primarily concerned with calculating descriptive statistics, specifically the means and percentages of the survey items. The results revealed that primary school EFL teachers need in-service professional development training to improve their English language proficiency skills and pedagogic knowledge. The interviews with principals and trainers supported the results found in the surveys. Moreover, the teachers encountered obstacles in engaging in a continuous professional advancement scheme.